The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.xkme.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Pruritus and Clinical, Dialysis-Related, and Patient-Reported Outcomes in Hemodialysis Patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
116
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(126 citation statements)
references
References 50 publications
6
116
2
2
Order By: Relevance
“…Although the prevalence estimates of CKD-aP in dialysis patients vary between epidemiological studies, patient-reported data from the Dialysis Outcomes and Practice Patterns Study (DOPPS) indicate that approximately two-thirds of hemodialysis patients have CKD-aP, 37% of which experience moderate-to-severe symptoms [ 6 ▪ ]. Despite its high prevalence, CKD-aP is overlooked by healthcare professionals and under-reported by patients in clinical practice; 17% of patients always or nearly always bothered by itch do not report their symptoms to anyone [ 5 , 11 ].…”
Section: Chronic Kidney Disease-associated Pruritus: Epidemiology Pathophysiology and Clinical Presentationmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the prevalence estimates of CKD-aP in dialysis patients vary between epidemiological studies, patient-reported data from the Dialysis Outcomes and Practice Patterns Study (DOPPS) indicate that approximately two-thirds of hemodialysis patients have CKD-aP, 37% of which experience moderate-to-severe symptoms [ 6 ▪ ]. Despite its high prevalence, CKD-aP is overlooked by healthcare professionals and under-reported by patients in clinical practice; 17% of patients always or nearly always bothered by itch do not report their symptoms to anyone [ 5 , 11 ].…”
Section: Chronic Kidney Disease-associated Pruritus: Epidemiology Pathophysiology and Clinical Presentationmentioning
confidence: 99%
“…CKD-aP is unpleasant and potentially debilitating for patients undergoing hemodialysis, and has been associated with worse clinical outcomes, including a greater risk of infection, hospitalizations, and mortality [ 6 ▪ , 23 ]. Data from DOPPS also showed that hemodialysis patients with extreme pruritus were more likely to withdraw from dialysis, miss scheduled dialysis sessions, and take a longer time to recover from dialysis treatment, compared with patients not bothered by pruritus [ 6 ▪ ].…”
Section: Burden Of Chronic Kidney Disease-associated Pruritus In Hemodialysis Patientsmentioning
confidence: 99%
See 3 more Smart Citations